Benjamin Church and the Origins of American Rangers - Hall, Garrett DeWayne (My University, 2016)
Benjamin Church was a Puritan from colonial New England. Church moved to the frontier where he befriended many of his Native American neighbors. Through those friendships, Church was able to pass between the cultural boundaries that separated native England and the Puritan settlements. Church maintained his loyalty to his Anglo- American community and his Christian faith, but also developed an appreciation for many elements of Native American culture. When King Philip’s War broke out between the New Englanders and several groups of Native Americans in the last quarter of the seventeenth century, Church fought for the English colonies. However, Church adopted many of the tactics he had learned from his Native American friends and used them against his enemies. Instead of following Native American allies into battle, Church recruited
I. INTRODUCTION 1 II. THE PEQUOT WAR: IDENTIFYING COLONIAL DEPENDENCE ON NATIVE AMERICAN ALLIES 23 III. BENJAMIN CHURCH: TWO WORLDS AND THE FOUNDATION FOR A TRANSCULTURAL MILITARY COMPANY 49 IV. BENJAMIN CHURCH: THE FORMATION OF A TRANSCULTURAL MILITARY COMPANY DURING KING PHILIP’S WAR 81 V. BENJAMIN CHURCH’S CONTRIBUTIONS TO KING WILLIAM’S WAR AND QUEEN ANNE’S WAR: THE ACCEPTANCE OF THE AMERICAN GUERILLA FIGHTER 103 VI. BENJAMIN CHURCH’S LEGACY: GORHAM, ROGERS, AND THE CONTINUED USE OF AMERICAN GUERLLIA FIGHTERS IN COLONIAL NEW ENGLAND 132 BIBLIOGRAPHY 158
Keywords: Thesis, Academic; History